Revision Approach for Optimum Design of Pressurized Irrigation Systems - , Alaa Nabil El-Hazek (Archives of Current Research International, 2016)
The great target for mankind is always to achieve the optimum use of available resources against the increasing food and other demands of the world population versus the shrinking resources. This paper provides snapshots of research and practical implementation of optimum design concepts and criteria of pressurized irrigation systems. Technical papers, reports and case studies are reviewed addressing revision approach for the optimum design of pressurized irrigation systems. The definition of the optimum irrigation has to be as widely as maximization of overall benefits including nonmonetary benefits; such as water quality protection and food security. Reliable information on irrigation methods is important for determining agricultural water demand trends. The model HYDRUS-2D can be employed to derive characteristic irrigation control functions to determine optimal irrigation times and water amounts. Also, a software application for Android mobile devices is available to evaluate the responsiveness of all available optimum commercial diameters to operational changes. The optimization of the irrigation system is an important factor to enhance water use efficiency. To get optimum pressurized irrigation systems, the common employed optimization techniques are linear programming, recursive design and genetic algorithm.